2014
DOI: 10.1159/000360930
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Brain Edema and Restoration of Functional Independence by Bevacizumab in Brain-Metastatic Breast Cancer: A Case Report

Abstract: Background: Brain metastases (BM) are an increasing challenge in modern oncology, as treatment options especially after exhaustion of local treatment approaches are very limited. Patient and Methods: A long-term surviving patient with brain-only metastatic breast cancer, who presented at our department with massive corticosteroid-refractory brain edema with serious neurological symptoms after exhaustion of all local therapy options, was started on bevacizumab. Results: Initiation of bevacizumab monotherapy led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…A number of previous case studies with small sample sizes have shown that bevacizumab is effective for brain edema by blocking the binding of VEGF-A to its receptors. [ 7 10 ] Wang et al [ 11 ] reported that in 8 patients with brain metastasis and severe brain edema, using a combination therapy of bevacizumab and stereotactic radiosurgery (Cyberknife) decreased the edema area by 63.4% in MRI T2 images. Recently, our case series study of 10 patients showed that bevacizumab therapy effectively relieved serious brain edema associated with reirradiation in patients.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous case studies with small sample sizes have shown that bevacizumab is effective for brain edema by blocking the binding of VEGF-A to its receptors. [ 7 10 ] Wang et al [ 11 ] reported that in 8 patients with brain metastasis and severe brain edema, using a combination therapy of bevacizumab and stereotactic radiosurgery (Cyberknife) decreased the edema area by 63.4% in MRI T2 images. Recently, our case series study of 10 patients showed that bevacizumab therapy effectively relieved serious brain edema associated with reirradiation in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the brain has long been considered an “immune-privileged” organ with limited capacity for inflammatory response, it is becoming clear that BM harbors an active inflammatory microenvironment that is capable of inducing prominent anti-tumor immune responses [43]. Because established BM contain considerable inflammatory infiltrates composed of various immune cells [44], the marked reduction of the large peritumoral edema on progressive NSCLC BM might reflect how silibinin-induced inhibition of STAT3 may increase the immunogenicity of BM cancer cells via cell-autonomous pathways and/or may favor the cell-nonautonomous reprogramming of the BM microenvironment (e.g., endothelial cells, tumor-associated macrophages, tumor-infiltrating lymphocytes) toward an immunostimulatory state [4548]. …”
Section: Discussionmentioning
confidence: 99%
“…Bevacizumab is a monoclonal antibody that targets the VEGF ligand and inhibits vascular proliferation. At present, there are only preliminary results of using bevacizumab in the treatment of BC-related brain metastases [ 8 , 9 , 10 , 11 , 12 ]. Prolonged responses with neurological progression-free survival times varying from 2.8 to 11 months have been observed.…”
Section: Discussionmentioning
confidence: 99%